Thermal model of a photovoltaic module with heat-protective film - Kirpichnikova, I.M.; Sudhakar, K.; Makhsumov, I.B.; Martyanov, A.S.; ShanmugaPriya, S. (Elsevier Ltd, 2022)
Research on reducing the working temperature of PV modules is gaining attention to improve their electrical performance, efficiency, and life especially in warm climatic conditions. This study describes the use of novel heat-protective film based on holographic coating with a total internal reflection prism layer applied to maintain the operating temperature of the photovoltaic module. A mathematical model of thermal protection based on the holographic film is described. MATLAB/Simulink simulation was used to estimate the current-voltage and output power–solar irradiance characteristics of a photovoltaic module with and without holographic film. Regression models were developed based on field testing to determine a relationship between the temperature of heat-protected/unprotected PV panels and ambient temperature. The results showed that a temperature reduction of 3.54 °C is obtained for solar modules with thermal protection film compared to the one without holographic film. The modeling and field performance results confirm the effectiveness of the thermal protective film in reducing the temperature and improving the photovoltaic panel performance in hot climates.